Analysis of purge gas temperature in cyclic TSA process - Ko, DH; Kim, M; Moon, I; Choi, DK (PERGAMON-ELSEVIER SCIENCE LTD, 2002)
This study analyzes the effect of an operating parameter on the dynamic behavior by performing dynamic simulations of cyclic thermal swing adsorption (TSA) system, in fixed beds packed with activated carbon as an adsorbent. This TSA process purifies and regenerates the ternary mixtures consisted of benzene, toluene and p-xylene. A mathematical model, considering the dynamic variation and spatial distribution of properties within the bed, has been formulated and described by a set of partial differential algebraic equations. The models are based on non-equilibrium, non-isothermal and non-adiabatic conditions. The breakthrough curves of our simulation model are compared with those of Yun's experiments (1999). The cyclic steady-state (CSS) cycles are obtained for the various cases by cyclic simulation. The influences of the purge gas temperature on breakthrough curves, CSS convergence time, cyclic operating step tine, purge gas consumed, regeneration energy requirement and adsorption ability at CSS are also discussed. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: THERMAL REGENERATION; ADSORPTION BEDS; SOLUTE CONDENSATION; PARAMETRIC ANALYSIS; EQUILIBRIUM-THEORY; SINGLE SOLUTES; FIXED-BED; DESORPTION